The role and importance of family entrepreneurship in sports tourism - Miočić, Josip (Oeconomica Jadertina, 2019)
This paper explores two basic elements of entrepreneurship: family entrepreneurship on the one hand, with its basic features and specificities as a component of entrepreneurship in general, and family entrepreneurship in the field of sports tourism, as a separate branch of entrepreneurship created by allocating productive resources to the subject activity - tourism, which can presently be a segmental factor for the economy of the Republic of Croatia in general. Also, the influence of family entrepreneurship in tourism is determined from the point of view of the creation of new accommodation capacities and the growth of the number of arrivals of domestic and foreign guests in Zadar County. The aim of the paper is to highlight the increasing role and importance of family entrepreneurship in the field of sports tourism. The paper defines recommendations and guidelines for stronger and vigorous development of family business with an emphasis on sports tourism in order to enable better identification, monitoring of development and projection of the impact of family businesses in the field of sports tourism on the economy of the Republic of Croatia.
Keywords: entrepreneurship; family entrepreneurship; sport; tourism; economy